2011
DOI: 10.1128/aem.01388-10
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Molecular Epidemiological Study of Thermophilic Campylobacters on One Conventional Broiler Chicken Farm

Abstract: Improved understanding of the ecology and epidemiology of Campylobacter in the poultry farm environment is key to developing appropriate farm-based strategies for preventing flock colonization. The sources of Campylobacter causing broiler flock colonization were investigated on one poultry farm and its environment, from which samples were obtained on three occasions during each of 15 crop cycles. The farm was adjacent to a dairy farm, with which there was a shared concreted area and secondary entrance. There w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
1
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 44 publications
(45 reference statements)
3
42
1
4
Order By: Relevance
“…Some studies have identified a spatial relationship among genotypes, with isolates being more similar within rather than among farms (French et al, 2005;Kwan et al, 2008a;Rotariu et al, 2009). These data suggest that differences may be maintained among farms by localized transmission and continual reinfection, whilst animal movements on a regional scale may contribute to overall homogeneity of Campylobacter diversity (Ridley et al, 2011). Scottish cattle and sheep have been shown to harbour different Campylobacter populations, despite sharing the same farm environment (Sproston et al, 2011), and while the genotypes of Campylobacter isolates from pet dogs are diverse, they exhibit a high degree of similarity to human disease isolates (Parsons et al, 2009).…”
Section: Campylobacter In Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have identified a spatial relationship among genotypes, with isolates being more similar within rather than among farms (French et al, 2005;Kwan et al, 2008a;Rotariu et al, 2009). These data suggest that differences may be maintained among farms by localized transmission and continual reinfection, whilst animal movements on a regional scale may contribute to overall homogeneity of Campylobacter diversity (Ridley et al, 2011). Scottish cattle and sheep have been shown to harbour different Campylobacter populations, despite sharing the same farm environment (Sproston et al, 2011), and while the genotypes of Campylobacter isolates from pet dogs are diverse, they exhibit a high degree of similarity to human disease isolates (Parsons et al, 2009).…”
Section: Campylobacter In Animalsmentioning
confidence: 99%
“…In one study of free-range chickens, the STs recovered at two separate locations were similar at the same time and could not be predicted by farm location, despite flocks being exposed to different local environments through minimal biosecurity (Colles et al, 2008b). Biosecurity remains a high priority in reducing Campylobacter levels in chickens, however, and MLST typing of strains provides a means by which 'environmental contamination' can more accurately be defined and attributed to agricultural or wildlife sources (Ridley et al, 2011).…”
Section: Campylobacter In Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, 431 verified human campylobacteriosis cases were identified in Poland, with a low infectious rate (1.12 per 100 000), but this small number of infections may be due to an inadequate laboratory identification system (5). Poultry meat is the most important source of Campylobacter infection, especially with C. jejuni (5,6,8,10,18). It is estimated that 50% to 80% of human campylobacteriosis cases have been attributed to the chicken (broiler) reservoir (5).…”
Section: Introductionmentioning
confidence: 99%
“…Poultry are asymptomatic carriers of Campylobacter and the infected flocks cannot be identified by clinical symptoms in birds (Berry et al 1988, Newell et al 2001, Newell and Fearnley 2003, Wieczorek and Osek 2005, Adkin et al 2006, Bull et al 2006, Allen et al 2007, Wirz et al 2010, Hue et al 2011, Ridley et al 2011, Habib et al 2012. The contamination of broiler meat with C. jejuni or C. coli from the chicken intestine may occur during slaughter processing through several routes, such as the air, water, previously slaughtered Campylobacter-positive flocks, equipment used in abattoirs, insects or slaughterhouse personnel (Rivoal et al 1999, Newell et al 2001, Nauta et al 2007, Normand et al 2008, Reich et al 2008, Wirz et al 2010, Hue et al 2011, Habib et al 2012).…”
mentioning
confidence: 99%